Early neurological deterioration after subarachnoid haemorrhage: risk factors and impact on outcome. Issue 3 (25th September 2012) - Helbok, Raimund; Kurtz, Pedro; Vibbert, Matthew; Schmidt, Michael J; Fernandez, Luis; Lantigua, Hector; Ostapkovich, Noeleen D; Connolly, Sander E; Lee, Kiwon; Claassen, Jan; Mayer, Stephan A; Badjatia, Neeraj
Abstract : Background: Early neurological deterioration occurs frequently after subarachnoid haemorrhage (SAH). The impact on hospital course and outcome remains poorly defined. Methods: We identified risk factors for worsening on the Hunt–Hess grading scale within the first 24 h after admission in 609 consecutively admitted aneurysmal SAH patients. Admission risk factors and the impact of early worsening on outcome was evaluated using multivariable analysis adjusting for age, gender, admission clinical grade, admission year and procedure type. Outcome was evaluated at 12 months using the modified Rankin Scale (mRS). Results: 211 patients worsened within the first 24 h of admission (35%). In a multivariate adjusted model, early worsening was associated with older age (OR 1.02, 95% CI 1.001 to 1.03; p=0.04), the presence of intracerebral haematoma on initial CT scan (OR 2.0, 95% CI 1.2 to 3.5; p=0.01) and higher SAH and intraventricular haemorrhage sum scores (OR 1.05, 95% CI 1.03 to 1.08 and 1.1, 95% CI 1.01 to 1.2; p<0.001 and 0.03, respectively). Early worsening was associated with more hospital complications and prolonged length of hospital stay and was an independent predictor of death (OR 12.1, 95% CI 5.7 to 26.1; p<0.001) and death or moderate to severe disability (mRS 4–6, OR 8.4, 95% CI 4.9 to 14.5; p=0.01) at 1 year. Conclusions: Early worsening after SAH occurs in 35% of patients, is predicted by clot burden and is associated with mortality and poor functional outcome at 1 year.